Pengaruh Edukasi Gizi Terhadap Asupan Makan dan Sisa Makan Pasien Rawat Inap Diabetes Melitus di RS DKT TK IV 02.07.04 Bandar Lampung - Anjani, Kartika Eka Putri; Kustiani, Ai (Journal of Citizen Research and Development, 2025)
Diabetes Mellitus is a chronic disease that requires proper diet management to prevent complications. Nutrition education is an important intervention in helping patients manage their diet according to nutritional needs. This study aims to analyze the effect of nutritional education on food intake and food waste in inpatients with Diabetes Mellitus at DKT TK IV Hospital 02.07.04 Bandar Lampung. This research uses a quasi-experimental design with a pretest-posttest approach. The research subjects were Diabetes Mellitus inpatients involving 35 respondents with an age range of 29-61 and were given nutrition education. The Kolmogorov-Smirnov normality test was used to ensure data distribution, and parametric statistical analysis t test was used to test the effect of nutrition education. The results showed that the data was normally distributed, and there was a significant increase in food intake and a significant decrease in patient food waste after being given nutrition education. This shows that nutritional education effectively increases patient awareness and compliance with the recommended diet.